1994
DOI: 10.1002/bjs.1800810540
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of elderly patients with large bowel cancer

Abstract: The effect of age on the presentation, diagnosis, management and survival of patients with colorectal cancer was studied prospectively in 512 patients admitted to a single institution. In all, 225 patients were aged 70 years or more and 287 less than 70 years. Older patients had a significant excess of emergency presentations (18 versus 11 per cent). Methods of diagnosis, proportion of curative operations performed, stage and histological grade were similar in the two age groups. The postoperative mortality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
59
0
10

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 31 publications
(1 reference statement)
4
59
0
10
Order By: Relevance
“…This is a political decision that a physician should not have to face (Sulmasy, 1992). It has been demonstrated that strategies to improve the prognosis of colorectal cancer should not exclude the older patients (Mulcahy et al, 1994), and our small prospective series contributes to this conclusion. This is a small series of data, but one that deals with an important area.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…This is a political decision that a physician should not have to face (Sulmasy, 1992). It has been demonstrated that strategies to improve the prognosis of colorectal cancer should not exclude the older patients (Mulcahy et al, 1994), and our small prospective series contributes to this conclusion. This is a small series of data, but one that deals with an important area.…”
Section: Discussionmentioning
confidence: 69%
“…A difference in the clinical presentation is being reported (Arnaud et al, 1991) as a consequence of a twofold increase in right-sided cancers, which are responsible for occult bleeding, occlusion and nutritional impairment. Obstructing tumours are significantly more common in patients over 70 years of age (Korenaga et al, 1991), requiring emergency operation; this is associated with a significantly higher incidence of operative deaths at any age (Turunen et al, 1983;Irvin, 1988), but the prevalence of operative morbidity and mortality among the aged on emergency is significantly higher than for younger patients under the same conditions, in both eastern and western series (Korenaga et al, 1991;Mulcahy et al, 1994). When only elective operations are considered, any difference in operative deaths recorded in the two age groups is small, ranging from 4% to 7% (Arnaud et al, 1991;Mulcahy et al, 1994).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Emergency colon surgery itself had a higher mortality rate than non-emergency colon surgery [2,[12][13][14]. The present study is of potential interest because sepsis is a very common problem in elderly patients who undergo emergency colorectal surgery.…”
Section: Discussionmentioning
confidence: 76%